Indigenous Cellulosic Raw Materials for the Production of Pulp, Papers and Board - Bhat, R. V.; Jaspal, Narendra S. (Indian Forester, 1957)
Laboratory experiments on the production of wrapping papers from castor stem (Ricinus communis Linn.) of the annual variety are described. Wrapping papers Were made on the pilot plant of the Forest Research Institute from 100% castor stem pulp and also from a mixture of 70% of this pulp and 30% bamboo kraft pulp. These papers were characterised by good formation and satisfactory strength properties. A sample of wrapping paper made on the pilot plant is included in this publication. The utilization of castor stalk for the manufacture of wrapping papers will depend upon the price at which it can be made available at the mill site.